Characterization of Hormonal, Metabolic, and Inflammatory Responses in CrossFit® Training: A Systematic Review - Jacob, Nacipe; Novaes, Jefferson S.; Behm, David G.; Vieira, João G.; Dias, Marcelo R.; Vianna, Jeferson M. (Frontiers in Physiology, 2020)
Background: CrossFit® training is a high-intensity functional training program that aims to increase physical functional performance through biochemical responses, i.e., hormonal, metabolic and inflammatory responses. Most hormonal, metabolic and inflammatory changes induced by CrossFit® training have been reported in isolated clinical studies. The purpose of this review was to systematically explore the existing literature on characterization of hormonal, metabolic, and inflammatory responses resulting from CrossFit® training. Methods: A systematic search of the literature was conducted in PubMed, Web of Science and Scopus from August 2019 to October 2019. Studies were selected through critical review of the content. Using specific keywords, 623 articles were found, of which 597 were excluded for ineligibility, and 25 were eligible. The papers were separated according to subject area: hormonal (n = 8), metabolic (n = 19), and inflammatory (n = 6) changes. All were published between 2015 and 2019. Results: This review reveals potential effects of CrossFit® training on hormonal, metabolic and inflammatory parameters. However, studies had low levels of evidence and reliability due to methodological limitations. Conclusion: In summary, the results are of paramount importance for improving understanding of the effects of CrossFit® training and serve as a basis for prescribing future exercise protocols.